PENERAPAN MODEL PEMBELAJARAN PAIRED STORYTELLING UNTUK MENINGKATKAN KETERAMPILAN MENYIMAK CERITA SISWA KELAS V SDN 1 ARAWA KABUPATEN SIDENRENG RAPPANG - Nur Ilmi; Aprilia, Dian; Abdul Hakim (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The study's goals are to: 1) Determine how the Paired Storytelling learning paradigm may be used to enhance students' story listening comprehension in class V SDN 1 Arawa. 2) To determine if using the Paired Storytelling learning methodology may help students in class V SDN 1 Arawa become better story listeners. This study uses a qualitative methodology and is classified as classroom action research. This paper investigates the teacher's learning process and the learning outcomes of the students using the Paired Storytelling learning paradigm. The subjects of the research were twenty-four teachers and V grade pupils. Data collecting techniques include observation, testing, and documenting among others. Additionally, descriptive qualitative analysis and processing were performed on the data. The effectiveness of this research will be determined by how well the student learning outcomes and the paired storytelling implementation procedure work together. While the findings of research in cycle II have met the set success indicator of ≥76%, the results of cycle I research have not yet reached the success indicator of the results set because students are still less engaged in their learning. According to the findings, fifth-grade students at SDN 1 Arawa may enhance their listening abilities by using the Paired Storytelling learning paradigm.